Effectiveness and safety of biosimilar infliximab (CT-P13) in a real-life setting in patients with Crohn's disease or ulcerative colitis. (1st January 2019) - Gheorghe, Cristian; Svoboda, Pavel; Mateescu, Bogdan
Abstract: Objective: To assess the effectiveness and safety of biosimilar infliximab (CT-P13) in a real-life setting in adults with moderate-to-severe active Crohn's disease (CD) or ulcerative colitis (UC). Methods: This multi-centre, observational cohort study was conducted at medical centres in Romania, Czech Republic, and Bulgaria. Effectiveness was measured using the Crohn's Disease Activity Index (CDAI) for CD or partial Clinical Activity Index (pCAI) for UC. Quality-of-life (QoL) was measured using the Short Inflammatory Bowel Disease Questionnaire (SIBDQ). Safety was assessed according to treatment withdrawals and adverse events (AEs) monitoring. Analyses were performed in the safety population and were reported based on the observed case (OC) or last observation carried forward (LOCF) method. Results: Altogether, 85 patients with CD ( n  = 38) or UC ( n  = 47) received biosimilar infliximab for up to 30 weeks. Most patients ( n  = 68; 80.0%) had no prior exposure to infliximab. At the end of treatment, 65.8% (95% CI = 49.8–78.9) of CD patients and 55.3% (95% CI = 41.2–68.6) of UC patients showed a clinical response, and 47.4% (95% CI = 32.5–62.7) and 48.9% (95% CI = 35.3–62.8), respectively, were in remission. Statistically significant ( p  < 0.0001) improvements from baseline were observed in CDAI and pCAI scores (both LOCF). In the combined CD and UC population, SIBDQ was significantly improved ( p  < 0.0001) from baseline to end of treatment (OC). Two AEs (moderately severe infusion reactions) were judged by investigators to be definitely related to treatment, one of which led to treatment withdrawal. Conclusion: Results align with those of previous studies demonstrating the effectiveness and safety of biosimilar infliximab in CD and UC.